KOMUNIKASI TERAPEUTIK ISLAM DALAM DZIKIR KINESTETIK MENGHADAPI PANDEMI COVID 19: (Studi Kasus Kearifan Lokal Pondok Pesantren Singa Putih dengan Pendekatan Teori Interaksionisme Simbolik) - Dianis Nurwati; Putri Widowati, Ajeng; Tanisya Agustin, Pinky; Mimayanti, Linda Devita (HERITAGE, 2024)
In the midst of the strengthening impact of stress due to the uncertain situation of the Covid19 pandemic, the role of figures society, especially Kyai, is needed in providing stimulus to form patterns of behavior in society. Correct Islamic therapeutic communication has the potential to help give meaning to individuals in responding to the Covid19 pandemic situation. Kinesthetic dhikr therapy is then present as part of the solution to problems that arise in dealing with the Covid19 pandemic, namely reducing the level of anxiety, depression, and stress in society, especially students. Kinesthetic dhikr is an activity of remembering God through a special do'a-do'a that is carried out by involving movements and massages at several crucial points in the limbs. This study used a mix methode research, the subjects of the study were 99 students of the Modern White Lion Islamic Boarding School which were divided into 3 different experimental groups. This study aims to describe the process of meaning formation in therapeutic communication activities packaged through the medium of kinesthetic dhikr, based on the correlation of Islamic therapeutic communication and kinesthetic dhikr in reducing anxiety levels, as well as seeing differences in the effectiveness of each treatment. The results showed that there were changes in the level of anxiety, depression, and stress in students as measured by the DAS Scale measurement instrument before and after being given kinesthetic dhikr treatment by being proven using a simple Electrograph complement medium.